Gene expression changes in tumor free tongue tissue adjacent to tongue squamous cell carcinoma - Boldrup, Linda; Gu, Xiaolian; Coates, Philip J; Norberg-Spaak, Lena; Fahraeus, Robin; Laurell, Göran; Wilms, Torben; Nylander, Karin (Oncotarget, 2017)
Due to the high frequency of loco-regional recurrences, which could be explained by changes in the field surrounding the tumor, patients with squamous cell carcinoma of head and neck show poor survival. Here we identified a total of 554 genes as dysregulated in clinically tumor free tongue tissue in patients with tongue tumors when compared to healthy control tongue tissue. Among the top dysregulated genes when comparing control and tumor free tissue were those involved in apoptosis (CIDEC, MUC1, ZBTB16, PRNP, ECT2), immune response (IFI27) and differentiation (KRT36). Data suggest that these are important findings which can aid in earlier diagnosis of tumor development, a relapse or a novel squamous cell carcinoma of the tongue, in the absence of histological signs of a tumor.
Keywords: Tongue; Humans; Case-Control Studies; jazyk; lidé středního věku; studie případů a kontrol; Biomarkers, Tumor; Female; Aged; dospělí; senioři; lidé; RNA expression; nádorové biomarkery; Adult; staging nádorů; Follow-Up Studies; ženské pohlaví; field cancerization; Male; tongue cancer; Middle Aged; nádory jazyka; prognóza; stanovení celkové genové exprese; Aged, 80 and over; Tongue Neoplasms; senioři nad 80 let; spinocelulární karcinom; Carcinoma, Squamous Cell; Neoplasm Staging; Gene Expression Profiling; míra přežití; mužské pohlaví; Prognosis; následné studie; Survival Rate